VD_FINDINFO HC / 2014 / 936 vom 1. Dezember 2014 - VD Tribunal cantonal (2014)
ASSISTANCE JUDICIAIRE, DÉPENS, FRAISEN GÉNÉRAL | 106 al. 1 CPC (CH), 122 al. 1 let. b CPC (CH), 122 al. 1 let. d CPC (CH)